Humans gradually integrate sudden gain or loss of visual information into spatial orientation perception - Voros, Jamie; Kravets, Victoria; Smith, Kieran; Clark, Torin K. (Frontiers in Neuroscience, 2024)
Vestibular and visual information is used in determining spatial orientation. Existing computational models of orientation perception focus on the integration of visual and vestibular orientation information when both are available. These computational models capture well-documented differences in spatial orientation perception with visual information or without (i.e., in the dark). For example, during earth vertical yaw rotation at constant angular velocity without visual information, humans perceive their rate of rotation to decay. However, during the same sustained rotation with visual information, humans can continue to more accurately perceive self-rotation. Prior to this study, there was no existing literature on human motion perception where visual information suddenly become available or unavailable during self-motion. In a human psychophysical experiment, we obtained perceptual reports of self-rotation during various profiles of Earth-vertical yaw rotation, with transitions in the availability of visual information (and control conditions with visual information available throughout the motion or unavailable throughout). By quantifying the dynamic time course, we found that when visual orientation information suddenly become available, subjects gradually integrated the new visual information over ~10 seconds. In the opposite scenario (visual information suddenly removed), past visual information continued to impact subject perception of self-rotation for ~30 seconds. We present a novel computational model of orientation perception that is consistent with the experimental results presented in this study. The gradual integration of sudden loss or gain of visual information is achieved via low pass filtering in the visual angular velocity sensory conflict pathway. In conclusion, humans gradually integrate sudden gain or loss of visual information into their existing perception of self-motion.